Challenges and prospects of tracking informal cross border trade in COMESA region - Wanjiku, J.; Gelan, Ayele; Gbegbelegbe, Sika; Karugia, Joseph T.; Massawe, Stella C. (2011)
This paper reviews the informal cross border trade (ICBT) in major staple food products among selected Common Market for Eastern and Southern Africa (COMESA) member countries. Current adopted approaches and methods of estimating informal trade are discussed and the magnitude of informal trade ﬂows between countries are estimated. Few agencies in the region are monitoring the informal trade thus a lot of the data is unrecorded. The missing informal trade data leads to unreliable external trade statistics which might, in turn, aﬀect eﬀective formulation, implementation and monitoring of domestic and regional trade policies. If trade relationships among African countries have to be strengthened then it is essential to estimate real magnitude of informal cross border. Available informal trade data suggest that ICBT still represents a signiﬁcant proportion of regional cross-border trade. Uganda Bureau of statistics (UBOS), for example notes that informal cross border activities have overall grown in the past 10 years among east and southern African (ESA) countries. In eastern Africa, Uganda’s border monitoring survey, for example, indicates that in 2006, informal exports and imports ﬂowing from Uganda to its neighbouring countries increased. The results also show that informal trade volumes and values for maize, rice, beans and pulses account for 36 and 37 % of total trade volumes and values in the region respectively. This paper concludes that the operations of ICBT as it is now in COMESA region are not eﬀective to inform trade related decision making despite the high magnitude. There is need to enhance the ICBT monitoring activities through improvements in the quality of the informal trade data. Speciﬁc actions include increasing the number of border points monitored for informal trade as well as the need to identify borders with signiﬁcant trade for monitoring. All the monitoring activities should take account of seasonal trade patterns. It is also essential to strengthen partnerships between the various agencies involved in trade monitoring by having regional collaboration of all the stakeholders in the ICBT activities. This will enhance eﬃcient collection of adequate informal trade data.